The Role of Pseudomonas Putida in Bioremediation: a Review - Angraeni, Andi Tirta; Amelia, Nila; Hala, Yusminah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Aerobic gram-negative bacteria Pseudomonas putida is commonly found in soil and air. It is renowned for its extraordinary metabolic ability to break down various complex organic materials, such as aquaculture pollutants. This article discusses the role of P. putida in bioremediation and the ability of P. putida to break down organic compounds such as aromatic and aliphatic chemicals. This study identified key genetic traits and metabolic pathways that enhance the efficiency of bacterial bioremediation by synthesizing relevant literature using a descriptive qualitative approach. These results demonstrate the importance of utilizing the diverse characteristics of bacteria for innovative bioprocesses that can produce sustainably manufactured products, which in turn promotes biotechnology-based economic development and environmental sustainability.